Increased Disease Resistance and Enzyme Activity Induced by Ethylene and Ethylene Production of Black Rot Infected Sweet Potato Tissue - Stahmann, M. A. (1966)
Exposure of root tissue from a susceptible variety of sweet potato to low concentrations of ethylene induced a resistance to infection by Ceratocystis fimbriata and an increase in the activity of peroxidase and polyphenoloxidase in the tissue. Susceptible tissue that was inoculated with a pathogenic strain of C. fimbriata or a nonpathogenic strain that can induce resistance liberated more ethylene into closed chambers than tissue inoculated with strains that did not induce resistance. It is suggested that ethylene may be a stimulus that diffuses from infected areas into adjoining tissue to initiate metabolic changes which may lead to disease resistance. Polyphenol oxidase but not peroxidase activity was increased in slices of potato tubers and parsnip roots treated with ethylene. The activity of these enzymes in root tissue of carrot, radish or turnip was not altered by ethylene treatment.